2008
DOI: 10.1158/1535-7163.mct-07-2132
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery to mesothelioma cells using functionally selected internalizing human single-chain antibodies

Abstract: Mesothelioma is a malignancy of the mesothelium and current treatments are generally ineffective. One promising area of anticancer drug development is to explore tumor susceptibility to targeted therapy. To achieve efficient, targeted intracellular delivery of therapeutic agents to mesothelioma cells, we selected a naive human singlechain (scFv) phage antibody display library directly on the surface of live mesothelioma cells to identify internalizing antibodies that target mesothelioma-associated cell surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…Tumor-binding ligands such as peptides (8,9) and antibodies (10,11) may be conjugated to the distal terminus of PEGylated nanoparticles and macromolecules to increase targeting specificity. Thus far, various tumor-associated antigens or receptors have been validated as targets for PEGylated compounds, especially for immunoliposomes (10)(11)(12)(13)(14)(15). These tumor-associated antigens or receptors can be either endocytic or nonendocytic.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-binding ligands such as peptides (8,9) and antibodies (10,11) may be conjugated to the distal terminus of PEGylated nanoparticles and macromolecules to increase targeting specificity. Thus far, various tumor-associated antigens or receptors have been validated as targets for PEGylated compounds, especially for immunoliposomes (10)(11)(12)(13)(14)(15). These tumor-associated antigens or receptors can be either endocytic or nonendocytic.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main advantage of the present system over the old screening system, which required handling a "polyclonal" pool of mAbs. 6,7 The innovative feature of our method is the use of PSIF as a fusion partner for antibodies in scFv format, thus facilitating the identification of antibody fragments capable of efficient internalization. The scFv fusion is much easier than the chemical conjugation of the antibody to a cytotoxic drug.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of potent cellinternalizing mAbs, however, requires labor-intensive screening of a massive number of candidates, and therefore the development of phage display-based methods to identify these candidates is highly desirable. 6,7 In the phage display-based method, a phage antibody library is added to the desired cells and then phages bound to the cell surface are removed. Only internalized phages are rescued from the intracellular compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Many preclinical studies have confirmed that immunoliposomal drugs targeted by means of scFv are more efficacious than either free drugs or non-targeted liposomal drugs [30,55,70,86,93,94]. In vitro studies by An et al demonstrated that immunoliposomal topotecan targeted by means of an scFv directed against mesothelioma cells were more efficacious than non-targeted liposomal topotecan or the free drug [94].…”
Section: Efficacy Of Immunoliposomal Drugs Targeted By Means Of Scfvmentioning
confidence: 99%
“…In vitro studies by An et al demonstrated that immunoliposomal topotecan targeted by means of an scFv directed against mesothelioma cells were more efficacious than non-targeted liposomal topotecan or the free drug [94]. Recently, Noble et al demonstrated that immunoliposomal vincristine or vinblastine targeted by an anti-HER2 scFv were more efficacious than their respective non-targeted formulations or the free drug, in an animal model of breast cancer [86].…”
Section: Efficacy Of Immunoliposomal Drugs Targeted By Means Of Scfvmentioning
confidence: 99%